Left ventricular assist device implantation by bi‐thoracotomy technique: A single‐center perspective. Issue 7 (16th April 2021) - Stoeckl, Elizabeth M.; Smith, Jason W.; Dhingra, Ravi; Fiedler, Amy G.
Abstract: Background: Left ventricular assist devices (LVAD) are standardly implanted via full sternotomy. Nonsternotomy approaches are gaining popularity, but potential benefits of this approach have not been well‐studied. We hypothesized that LVAD implantation by bi‐thoracotomy (BT) would demonstrate smaller and more consistent inflow cannula angles leading to improved postoperative outcomes compared to sternotomy. Methods: Charts of patients who underwent LVAD implantation between June 2018 and June 2020 at a single academic institution were retrospectively reviewed. Patient demographics, surgical approach (sternotomy vs. BT), laboratory values, and postoperative course were compared. The inflow cannula angle was measured on the first chest radiograph available postoperatively. Results: Of 40 patients studied, BT approach was used in 17 (42.5%). Mean inflow cannula angles were smaller in BT patients (23.0 vs. 37.1 degrees, p  = .018) and had a smaller standard deviation (13.8 vs. 20.3). Excluding patients who went on to receive a heart transplant or died in the same hospitalization, there was no difference in median length of hospital stay after surgery (16.0 vs. 17.5 days, p  = .768). However, BT patients required fewer days of postoperative inotrope support (4.0 vs. 7.0 days, p  = .012). Conclusions: Our data suggest inflow cannula angles are smaller and more consistent with the BT approach, which leads to a shorter duration of postoperative inotropic support. This finding may suggest improved right heart function following LVAD implant via BT approach. Further study is warranted to determine additional benefits of the BT approach.